A Systematic Literature Review on Enhancing Democratic Participation Through Civic Skills - Tiara Ernita; Suyato Suyato (Journal of Moral and Civic Education, 2026)
Research on civic skills has gained growing attention in recent decades, yet comprehensive syntheses of its development remain limited. Civic skills are fundamental to promoting democratic participation, social responsibility, and global citizenship. This study conducts a Systematic Literature Review (SLR) combined with bibliometric analysis to examine the evolution, trends, and thematic focus of civic skills research. Using the term “civic skills” in article titles, abstracts, and keywords within the Scopus database, 287 publications from 2004 to 2025 were analyzed. Data were processed using VOSviewer to identify major clusters, authorship networks, and citation patterns. The analysis reveals a significant increase in civic skills research after 2010, aligning with the rise of digital citizenship and global education. Four key clusters emerged: (1) civic engagement and participation, (2) critical thinking and communication, (3) digital and media literacy, and (4) civic education and curriculum development. Notably, the digital and media literacy cluster fundamentally redefines democratic participation in the 21st century transforming it from conventional civic involvement into digitally mediated, participatory, and network-based engagement. This shift highlights digital competence and ethical online behavior as essential civic skills for modern democracy. The study concludes that integrating digital literacy into civic education is vital for preparing active, critical, and responsible citizens. Future research should include multilingual databases to broaden analytical scope and generalizability. Keywords: Civic skills, Digital literacy, Civic education, Democratic participation, Bibliometric analysis